2018
DOI: 10.31357/jtfe.v8i1.3479
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Volatile Profiling of Azadirachta indica Leaves for the Management of Maize Weevil, Sitophilus zeamais (Motsch.) Infestations

Abstract: Neem (Azadirachta indica A. juss), is known to possess a wide range of pharmacological properties and is thus commercially exploitable. Apart from its medicinal potential, a considerable progress has been achieved regarding biological potential and chemical composition of the leaves which is an ever-increasing interest to the scientific community. During this study, biological phenomena and secondary metabolite composition of A. indica leaves were examined in the management of Sitophilus zeamais on stored maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Mahogany for example has been reported to possess several volatiles (Baba et al, 2020) some of which serve as olfactory cues that attract insect pests to the tree. The insecticidal and repellent potential of neem have also been evaluated on weevils and were reported to be effective (Perera et al, 2018).…”
Section: Repellent Effect Of Surfaces Treated With Plant Extractsmentioning
confidence: 99%
“…Mahogany for example has been reported to possess several volatiles (Baba et al, 2020) some of which serve as olfactory cues that attract insect pests to the tree. The insecticidal and repellent potential of neem have also been evaluated on weevils and were reported to be effective (Perera et al, 2018).…”
Section: Repellent Effect Of Surfaces Treated With Plant Extractsmentioning
confidence: 99%
“…The last compounds that are organosulfurate are part of the plant's defense mechanism against insect attacks. Compound 3,4-dimethyliophene was detected using HS-SPME/GC-MS in volatiles in the neem leaf (Perera et al, 2018) and identified in garlic essence oil (Allium sativum) (Satyal et al, 2017).…”
Section: Analysis Of Volatile Substances By Gc-msmentioning
confidence: 99%